SOCIO-CULTURAL ADAPTATION OF CHILDREN-ORPHANS BY LITERATURE - N. Yushkina (Вестник университета)
In Russian institutions for orphans there is a large number of children who need to be socialized for living in society. However, the proportion of graduates of orphanages that have successfully passed through socialization remains low. The article presents data of a sociological study in which features of sociocultural adaptation of orphans through literature were studied. A comprehensive approach, semi-formalized interviews with orphaned children was used to collect information. The obtained data allow to draw conclusions about the high value of fiction in the modern system of socialization of orphans. The presence of cultural samples with which the child could identify himself is revealed, which proves the existence of an important mechanism of socialization through literature, as well as the need for a more comprehensive and targeted proposal in the domestic literature.